Respectable outness: Examining the coming-out narratives of Latin American Lesbian, Gay, and Bisexual YouTube celebrity vloggers - García Rabines, Diego Rafael (2023)
Lesbian, Gay, and Bisexual YouTube celebrities have come to the limelight of popular media culture. This article explores how 10 of the most popular and influential YouTubers from three Latin American countries (Argentina, Colombia, and Mexico) have come to occupy lesbian, gay, and bisexual subject positions in their coming out vlogs. We argue that through the entwinement of YouTube’s political economy of celebrity and performances of respectability, these vloggers were able to turn their coming-outs into a form of emotional labor that positions them as exemplary models of queer success within the neoliberal economy and cultural regime